Home sweet murder [compact disc, unabridged] : true-crime thrillers - Patterson, James, 1947- (Hachette Audio, 2018)
Two true-crime tales relate the stories of a couple who were tortured and left for dead after a home invasion, and a double homicide in Omaha, Nebraska.